Triptolide Suppressed the Microglia Activation to Improve Spinal Cord Injury Through miR-96/IKKβ/NF-κB Pathway. Issue 12 (15th June 2019) - Huang, Yang; Zhu, Ning; Chen, Tao; Chen, Weijie; Kong, Jinsong; Zheng, Wenbiao; Ruan, Jianwei
Abstract : Study Design: The effect of triptolide on spinal cord injury (SCI) and inflammatory response was observed by establishing SCI rat model. And in vitro experiments were conducted to determine the underlying mechanism of triptolide-mediated in murine microglial cell line BV2. Objective: To determine the underlying mechanism of triptolide in suppressing the microglia activation to improve SCI. Summary of Background Data: Triptolide, as a major active ingredient of Chinese herb Tripterygium wilfordii, can promote spinal cord repair through inhibiting microglia activation, but the underlying mechanism is not clear. Methods: Locomotion recovery was accessed by Basso, Beattie, and Bresnahan score, the number of footfalls, stride length, and angle of rotation analysis. Expressions of microRNA 96 (miR-96), microglia activation marker Iba-1, and IκB kinase (IKKβ)/nuclear factor (NF)-κB-related proteins were detected by qRT-PCR or western blot. Inflammatory cytokines tumor necrosis factor-α and interleukin -1β were measured by enzyme-linked immuno sorbent assay. The regulation of miR-96 on IKKβ was confirmed by dual luciferase reporter assay. Results: Triptolide promoted locomotion recovery of SCI rats, upregulated the expression of miR-96, decreased microglia activation marker Iba-1 and IKKβ/NF-κB-related proteins, and inhibited inflammatory cytokines tumor necrosis factor-α and interleukin-1β levels in spinal cord tissues and lipopolysaccharide -induced microglia. Triptolide suppressed the microglia activation and inflammatory cytokines secretion in BV2 cells through up-regulating miR-96. We confirmed the interaction between miR-96 and IKKβ, and IKKβ expression was negatively regulated by miR-96. Finally, we determined that triptolide suppressed the microglia activation and inflammatory cytokines secretion through miR-96/IKKβ pathway. Conclusion: Triptolide suppressed microglia activation after SCI through miR-96/IKKβ/NF-κB pathway. Level of Evidence: N/A Abstract : Triptolide promoted locomotion recovery of SCI rats, upregulated the expression of miR-96, decreased microglia activation marker Iba-1 and IKKβ/NF-κB-related proteins, and inhibited inflammatory cytokines TNF-α and IL-1β levels in spinal cord tissues and LPS-induced microglia. Triptolide suppressed the microglia activation and inflammatory cytokines secretion in BV2 cells through upregulating miR-96.